Mechanosensitivity of microdomain calcium signalling in the heart. (November 2017) - Schönleitner, Patrick; Schotten, Uli; Antoons, Gudrun
Abstract: In cardiac myocytes, calcium (Ca 2+ ) signalling is tightly controlled in dedicated microdomains. At the dyad, i.e. the narrow cleft between t-tubules and junctional sarcoplasmic reticulum (SR), many signalling pathways combine to control Ca 2+ -induced Ca 2+ release during contraction. Local Ca 2+ gradients also exist in regions where SR and mitochondria are in close contact to regulate energetic demands. Loss of microdomain structures, or dysregulation of local Ca 2+ fluxes in cardiac disease, is often associated with oxidative stress, contractile dysfunction and arrhythmias. Ca 2+ signalling at these microdomains is highly mechanosensitive. Recent work has demonstrated that increasing mechanical load triggers rapid local Ca 2+ releases that are not reflected by changes in global Ca 2+ . Key mechanisms involve rapid mechanotransduction with reactive oxygen species or nitric oxide as primary signalling molecules targeting SR or mitochondria microdomains depending on the nature of the mechanical stimulus. This review summarizes the most recent insights in rapid Ca 2+ microdomain mechanosensitivity and re-evaluates its (patho)physiological significance in the context of historical data on the macroscopic role of Ca 2+ in acute force adaptation and mechanically-induced arrhythmias. We distinguish between preload and afterload mediated effects on local Ca 2+ release, and highlight differences between atrial and ventricular myocytes. Finally, we provide an outlook for further investigation in chronic models of abnormal mechanics (eg post-myocardial infarction, atrial fibrillation), to identify the clinical significance of disturbed Ca 2+ mechanosensitivity for arrhythmogenesis.